Correlation between clinical characteristics and antibody levels in COVID-19 convalescent plasma donor candidates - Uzun, Günalp; Müller, Rebecca; Althaus, Karina; Becker, Matthias; Marsall, Patrick; Junker, Daniel; Nowak-Harnau, Stefanie; Schneiderhan-Marra, Nicole; Klüter, Harald; Schrezenmeier, Hubert; Bugert, Peter; Bakchoul, Tamam (Viruses, 2023)
COVID-19 convalescent plasma (CCP) with high neutralizing antibodies has been suggested in preventing disease progression in COVID-19. In this study, we investigated the relationship between clinical donor characteristics and neutralizing anti-SARS-CoV-2 antibodies in CCP donors. COVID-19 convalescent plasma donors were included into the study. Clinical parameters were recorded and anti-SARS-CoV-2 antibody levels (Spike Trimer, Receptor Binding Domain (RBD), S1, S2 and nucleocapsid protein) as well as ACE2 binding inhibition were measured. An ACE2 binding inhibition < 20% was defined as an inadequate neutralization capacity. Univariate and multivariable logistic regression analysis was used to detect the predictors of inadequate neutralization capacity. Ninety-one CCP donors (56 female; 61%) were analyzed. A robust correlation between all SARS-CoV-2 IgG antibodies and ACE2 binding inhibition, as well as a positive correlation between donor age, body mass index, and a negative correlation between time since symptom onset and antibody levels were found. We identified time since symptom onset, normal body mass index (BMI), and the absence of high fever as independent predictors of inadequate neutralization capacity. Gender, duration of symptoms, and number of symptoms were not associated with SARS-CoV-2 IgG antibody levels or neutralization. Neutralizing capacity was correlated with SARS-CoV-2 IgG antibodies and associated with time since symptom onset, BMI, and fever. These clinical parameters can be easily incorporated into the preselection of CCP donors.
Gesehen am 08.08.2024